The economy of social resources and its influence on spatial perceptions - Gross, Elizabeth B.; Proffitt, Dennis (Frontiers in Human Neuroscience, 2013)
Survival for any organism, including people, is a matter if resource management. To ensure survival, people necessarily budget their resources. Our spatial perceptions contribute to resource budgeting by scaling the environment to our available resources. Effective budgeting requires setting a balance of income and expenditures around some baseline value. For social resources, this baseline assumes that the individual is embedded in their social network. A review of the literature supports the proposal that our visual perceptions vary based on the implicit budgeting of physical and social resources, where social resources, as they fluctuate relative to a baseline, can directly alter our visual perceptions.